Genetic population structure and fungicide sensitivity of Phytophthora betacei and P. infestans to systemic fungicides in isolates from tree tomato and potato in Colombia (2017)
The genus Phytophthora includes recognized plant pathogen species distributed worldwide which cause devastating diseases that affect many Solanaceae species. Applications of fungicides are often the main method to control these pathogens in the field. Monitoring the development of new resistant populations to common control molecules is central for designing integrated control strategies. This study focused on assessing the fungicide sensitivity of strains belonging to the species Phytophthora betacei and P. infestans, sampled in localities at the Central and Southern regions of the Andean mountains in Colombia. The main goals were to describe the variation in fungicide sensitivity to cymoxanil, mefenoxam, and fluopicolide by in vitro bioassays within and between two Phytophthora species and collection sites. All strains were molecularly characterized and the genetic population structure was assessed using twelve microsatellite markers. The fungicide in vitro assays showed a diverse response of the strains to the products used. Mefenoxam was the most effective of the three systemic fungicides tested...